Individual from the Viewpoint of Psychology and Sociology in the Context of Leisure Time-Library - Hasan Atmaca (Türk Kütüphaneciliği)
In today’s world, people are getting much stumbled with the changing conditions in such phenomena like rapid growth of cities, contemporary technologies and the relative growth of industry due to the latter requiring more and more information as ever before in order to recover themselves from this transition. Individuals can not reserve time for reading and thinking which is a prerequisite of knowledge due to lack of time created predominantly by the working conditions and some time-wasting traditions and customs especially they employ during their spare times. As being deprived of these activities fall individual to some certain psychological and sociological problems to some extent, the spare time option which have become the most necessary time interval for the individual to cover up his/her specific needs thereby to show progress in his characteristic components should be facilitated with the usage of libraries. Here that the libraries are for, especially outstanding as institutions to assist the individual in removing up both of the two problems mentioned above. It is a widely common fact that people who get to libraries and enhance their intellectual identity during their spare times have essentially provided a unity in their personalities from the physchological angle clenching their spiritual health as well as gaining new types of behaviors from the sociological approach also establishing permanent adaptation with others inside the community and with the nature and the giddy speed of technology